Nursing Now Brazil Campaign: alignments with global evidence for the development of national nursing - Isabel Amélia Costa Mendes; Ítalo Rodolfo Silva; Carla Aparecida Arena Ventura; Emerson Willian Santos Almeida; Manoel Carlos Neri da Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To analyze the goals and strategies of the Nursing Now Brazil Campaign in the light of global documents that focus on perspectives for the strengthening of Brazilian Nursing. Methods: Documentary research, carried out from the comparative analysis of the goals and strategies of the Nursing Now Brazil Campaign and documents with high global repercussion for social and economic development in the health context. Data were collected between May and July 2020. Results: The evidence set bases the need for strategies to achieve excellence in the training of nurses, better working conditions and the dissemination of successful experiences undertaken by these professionals in different health contexts for the strengthening of leadership and competencies capable of boosting socioeconomic development and people's quality of life. Conclusion: The achievement of the Nursing Now Brazil Campaign goals, based on global health evidence, may directly impact the socioeconomic development of the country.